PENYELESAIAN PERKARA TINDAK PIDANA PENCURIAN BUAH KOPI BERDASARKAN HUKUM ADAT BATAK KARO DI KECAMATAN BERASTAGI KABUPATEN KARO - Andika Bukit; Dessy Artina; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Petty theft or theft of small value that is now being tried in court is enough to attract the attention of the public. The general public considers that it is very unfair. For resolution, the community recognizes the enactment of the law nationally and also grows and develops a legal system that is based on habits that exist within the community. One area that still applies customary law as a rule that is obeyed by the community is the Karo Batak Custom. The purpose of writing this thesis, namely: First, to find out the settlement of cases of theft of coffee fruit Karo Batak customary law in the District of Berastagi Karo Regency. Second, to find out the obstacles in the implementation of the case of the theft of coffee fruit legally in the Batak Karo customary law in Berastagi District, Karo District. Third, to find out the legal consequences in the settlement of coffee theft cases legally in the Batak Karo adat law in Berastagi District, Karo District.This type of research can be classified as a type of sociological legal research, because in this study the author directly conducts research at the location or places under study to provide a complete and clear picture of the problem under study. This research was carried out in the Singa Village, Berastagi District, Karo District, while the population and sample were all sections related to this research, the data sources used were primary data, secondary data, and tertiary data, data collection techniques, namely interviews and studies literature.From the results of the research and discussion it can be concluded that, First, the process of settling cases of the theft of coffee fruit based on the customary law of the Batak Karo in Gurusinga Village consensus. Secondly, Barriers and efforts in resolving legal problems in the Batak Karo traditional law Lack of attention from the Regional Government and the many social influences or modernization. Third, the consequences of traditional law given in the settlement of cases of the theft of coffee fruit based on the Batak Karo customary law in Gurusinga Village, Berastagi District, Karo District, traditional legal responsibility by Rakut Sitelu / Daliken Sitelu as law enforcers and decided by Pengulu Kesain / Raja Urung with the put forward Runggu in Karo language (deliberation).Keywords: Settlement-Theft-Customary Law